Kepemimpinan Budaya Digital dalam Pendidikan Dasar - Idrus, Rahmawati; Perdana, Citra Ayu; Latif, Erna Yuliana (Cokroaminoto Journal of Primary Education, 2024)
We have entered an era of digital technology where individuals or organizations are obliged to fully embrace digital technology with ever-increasing change and improvement. Leaders must have skills and capabilities to use digital technology and apply these throughout the organization, to create a continuous improvement strategy that drives every data in their organization to change. This research focusses on developing a conceptual framework of such digital culture leadership for Elementary Education. It is proposed as a model for the attributes of the leaders of educational management in the digital age, encompassing: (1) Digital leadership, (2) Digital culture, (3) Change management, (4) Digital innovation and (5) Digital transformation. The factors within each of these categories are defined as follows; Digital leadership consists of five elements, which are vision, collaboration, management skills, digital literacy and innovation/creativity. Digital culture consists of four elements, which are collaboration, data-driven, customer centric, and innovation. Change management process consists of seven components, which are organizational structure, organization culture, strategy, decision making, process, technology and people. Digital innovation consists of three elements, which are digital application, change management and digital infrastructure. Through the proposed digital transformation processes applied to six organizational elements of strategy, staff, technology, data analytics, process and organizational culture, this research framework can be used as a way to enhance digital culture leadership with a vision for digital transformation. It provides a review methodology for the education administrator's current leadership practices, to suggest holistic improvements to management efficiency.